The effect of financial leverages on profitability: case study of the companies in manufacturing sector in Malaysia / Muhammad Afiq Rashdan - Rashdan, Muhammad Afiq (2022)
Using three businesses in Malaysia's manufacturing sector from 2011 to 2020, this study attempts to establish a theoretical relationship between financial leverage and profitability. The relationship between debt ratio, equity ratio, debt to equity ratio, debt to EBITDA and debt to capital ratio for financial leverage is investigated using the Net Profit Margin. Previous study demonstrates that some independent factors have a strong link with the dependent variable, which is the profitability of the Malaysia manufacturing sector, while others have a negligible relationship. This research is based on secondary data from three businesses in the manufacturing sector that are publicly traded on the Malaysian stock exchange, Bursa Malaysia. The collected data is examined using panel data in this study. The study's findings concentrated on descriptive analysis, correlation analysis, regression analysis, and hypothesis testing. The results of this research for regression analysis demonstrate that only one of the independent variables are significant to the profitability of the manufacturing sector in Malaysia, while the other four exhibits insignificant results. Aside from that, the correlation analysis results suggest that the independent factors, such as debt ratio, equity ratio and debt to equity ratio, have a positive association with the dependent variable, manufacturing sector profitability. Meanwhile, debt to capital ratio and debt to EBITDA ratio reveal that the profitability of the manufacturing sector is negatively related. According to the findings of this study, financial leverage has an impact on the profitability of Malaysia manufacturing sector. More variables for this study should be added, such as acid test ratio and total asset amount, according to the recommendations for this study. Aside from that, repeating and expanding the study to other industries, such as healthcare or technology sector, so that we can determine whether financial leverage has a meaningful impact on profitability.